Earthworms newly from Mongolia (Oligochaeta, Lumbricidae, Eisenia) - Robert Blakemore (ZooKeys, 2013)
Two new megadrile earthworms from the steppes, the first species wholly from Outer Mongolia, are ascribed to the partially parthenogenetic Eisenia nordenskioldi (Eisen, 1879) species-complex. Taxonomic justification of sympatric Eisenia nordenskioldi mongol and E. nordenskioldi onon ssp. n. are supported by mtDNA COI barcodes. The unreliability of molecular differentiation based on voucher names compared to definitive types is again demonstrated, as pertains to the ultimate Eisenia andrei Bouché, 1972 synonym of the E. fetida (Savigny, 1826) sibling species-complex composed of more than a dozen prior names. Similar species described from Northeast China [formerly Manchuria] and North Korea are briefly considered, albeit they are intermittently held in synonymy of cosmopolitan Aporrectodea rosea (Savigny, 1826) along with many other taxa including some exotic lumbricids initially found in India. Japanese and North American lumbricids are also mentioned. Distributions are discussed and an annotated checklist of all nine Siberian/sub-arctic E. nordenskioldi ssp. is appended.